Structural and stratigraphic history of the southern domain of the Indian Mountain Deformed Zone, southeastern New Brunswick, Canada: Tournaisian (Lower Carboniferous) tectonic ‘pop-up’ and collapse - Park, Adrian F.; St. Peter, Clint; Hinds, Steven J.; Stimson, Matthew R. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2024)
The southern domain of the Indian Mountain Deformed Zone (IMDZ) in southeastern New Brunswick marks a major right-lateral strike-slip fault belt active during late Tournaisian (Lower Carboniferous) sedimentation. The rocks of the Sussex Group, representing a depositional cycle from subsidence to basin inversion, occupy this zone and lie unconformable on crystalline basement, the latter representing a partially exhumed portion of the adjacent (to the south) buried Westmorland uplift. Deformation is related to early reverse faults/thrusts, later strike-slip faults. and latest normal faults. The Gorge Fault zone in the southern domain of the IMDZ demonstrates many essential features of the entire zone. The offset of The Gorge Fault zone increases to the east. In the west it forms a blind thrust and asymmetric anticline whereas in the east it expands into a reverse fault/thrust complex. A progressive evolution from reverse faults/thrusts to strike-slip fault movement resulted in a tectonic pop-up, culminating in gravitational collapse along normal faults with listric profiles that flatten out within 100–200 metres of the present erosion surface. Megabreccias formed during deposition of the Sussex Group are contemporary with reverse fault/thrusts. The geometry of the various faults is best explained by progressive deformation within an overall right-lateral strike-slip regime under general shear, with early formed features rotating both congruently and incongruently to the main IMDZ boundaries. Further complexity is a consequence of many reverse faults/thrusts and normal faults occurring close to a free surface and the latter a response to gravitational instability of the pop-up structure controlled by topography. A revised stratigraphy for the Sussex Group in the Indian Mountain Deformed Zone and its interpretation is integral to constructing the structural history. Two units, Stilesville Formation and Briggs Cross Formation, are formally defined here.